Mapping quality of service classes between UMTS, WiMAX and DiffServ/MPLS networks - Sarraf, C.M. (2013)
One of the major issues for Heterogeneous Wireless Access Networks (HWAN) or Next Generation Wireless Network (NGWN) is integrating the different wireless access technologies (e.g. GSM, GPRS, EDGE, UMTS, WiMAX, WLAN, etc) into a common platform. This integration should transparently provide mobile users unified and continuous services, including seamless handoff and real-time support of QoS. However, a real-time support of End-to-End QoS, in HWAN, is a challenging task that requires mapping of related messages as well as their associated attributes and parameters across all networks. In this paper, we present a novel method for mapping these messages and their attributes across UMTS, WiMAX and IP-Diffserv/MPLS networks. Â© 2013 IEEE.